Synthesis, surface activities, aggregation properties and oil washing performances of novel cardanol-based surfactants - Weiyang Liu; Congying Lu; Xin Zhao; Zuxi Zhang; Ruihong Huang; Lingxiao Fan; Wei Ding (PLoS ONE, 2026)
A mixed cardanol sulfonate surfactant (MYBS) of disubstituted styrene unsaturated cardanol sulfonate (2,4-YBS) and monosubstituted styrene unsaturated cardanol sulfonate (2-YBS) was synthesized by optimizing the optimal synthesis conditions of the three-step reaction of alkylation, sulfonation and neutralization. The molar percentages of the two are about 70%: 30%. Its structure was characterized by gas chromatography-mass spectrometry and infrared spectroscopy. At 25 °C, the surface tension of MYBS at critical micelle concentration (γCMC) and critical micelle concentration (CMC) was 33.32 mN/m and 0.676 mmol/L, respectively, which was better than that of traditional anionic surfactant (SDBS) and cardanol sulfonate surfactant (CDS). The thermodynamic parameters obtained from the conductivity measurements confirmed that the micellization process was a spontaneous and entropy-driven process. Dynamic light scattering test and transmission electron microscopy showed that MYBS molecules could form small spherical micelles of 10 nm-30 nm, which was consistent with the calculation results of critical packing theory. At the same time, the oil washing experiment confirmed that the oil washing efficiency can reach 73%, which provides technical support for the application of this kind of surfactant in improving oil recovery.